Role of nutritional composition in the development and survival of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) on artificial diet and natural hosts - Silva, Ivana F. da [UNESP]; Baldin, Edson Luiz L. [UNESP]; Specht, Alexandre; Roque-Specht, Vania F.; Morando, Rafaela [UNESP]; Malaquias, Juaci; Paula-Moraes, Silvana (Cambridge Univ Press, 2021)
Helicoverpa armigera is a pest of several crops causing significant economic impact. We evaluated the insect development on different vegetative and reproductive structures of cotton, maize, and soybean compared to artificial diet. One hundred individuals were evaluated per structure (cotton leaves and bolls; maize leaves, grains, and silk; soybean leaves and pods) and artificial diet. Centesimal analyses were performed on quantifiable nutrient contents in diets. The viability of immatures (eggs, larvae, and pupae) ranged from 30% on maize leaf to 74% on cotton bolls, while on the artificial diet, it was 70%. Maize, cotton, and soybean leaves provided viability of 30, 37, and 42%, respectively, revealing these leaves tissues are less favorable to the development of H. armigera immatures compared to 'reproductive tissues'. Centesimal composition of diets compared 14 common components in all diets, which correlated significantly with larval and pupal stages and/or pupal weight. Of the 12 dietary components that significantly affected larval development time, half were negatively correlated, indicating a decrease in developmental time from their increments. In general, when insects were confined separately to substrates, the artificial diet was the most suitable for H. armigera development compared to the evaluated natural diets. However, in natural conditions, the variability of available hosts must be considered. In addition, it is acceptable for moths to select more suitable hosts for oviposition, while their larvae move to other more suitable tissues of the same plant or even migrate to other plants.
Keywords: Biological development; biotic potential; centesimal composition; host suitability; nutrient content; old world bollworm